Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 641 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Crypturgus cinereus (J.F.W.Herbst, 1793)" ] } The dataset includes 641 records from 33 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0013732-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences